Screening for autism spectrum disorders in children with Down syndrome: population prevalence and screening test characteristics. - DiGuiseppi C; Hepburn S; Davis JM; Fidler DJ; Hartway S; Lee NR; Miller L; Ruttenber M; Robinson C; DiGuiseppi, Carolyn; Hepburn, Susan; Davis, Jonathan M; et al. (Journal of Developmental & Behavioral Pediatrics, 2010)
Objective: We assessed the prevalence of autism spectrum disorders (ASD) and screening test characteristics in children with Down syndrome.Method: Eligible children born in a defined geographic area between January 1, 1996, and December 31, 2003, were recruited through a population-based birth defects registry and community outreach, then screened with the modified checklist for autism in toddlers or social communication questionnaire, as appropriate. Screen-positive children and a random sample of screen-negative children underwent developmental evaluation.Results: We screened 123 children (27.8% of the birth cohort). Mean age was 73.4 months (range, 31-142). Compared to screen-negative children, screen-positive children had similar sociodemographic characteristics but a lower mean developmental quotient (mean difference: 11.0; 95% confidence interval: 4.8-17.3). Weighted prevalences of autistic disorder and total ASD were 6.4% (95% confidence interval [CI]: 2.6%-11.6%) and 18.2% (95% CI: 9.7%-26.8%), respectively. The estimated minimum ASD prevalence, accounting for unscreened children, is 5.1% (95% CI: 3.3%-7.4%). ASD prevalence increased with greater cognitive impairment. Screening test sensitivity was 87.5% (95% CI: 66.6%-97.7%); specificity was 49.9% (95% CI: 37.0%-61.4%).Conclusion: The prevalence of ASD among children with Down syndrome aged 2 to 11 years is substantially higher than in the general population. The modified checklist for autism in toddlers and social communication questionnaire were highly sensitive in children with Down syndrome but could result in many false positive tests if universal screening were implemented using current algorithms. Research needs include development of specific ASD screening algorithms and improved diagnostic discrimination in children with Down syndrome. Timely identification of these co-occurring diagnoses is essential so appropriate interventions can be provided.